Gamification in the Development of Historical Competence (Docentes 2.0 Journal, 2024)
Applying technologies generates active and immersive methods that require trainers to use appropriate procedures to improve their educational practice. Therefore, this article aimed to analyze the bibliographic sources on gamification in the development of historical competence between the years 2012-2022. This research was based on the systematic-hermeneutic method, hermeneutic-interpretative paradigm with a qualitative approach, systematic design of the literature, and descriptive documentary type; as a technique, the digital file was the support of the bibliographic manager Zotero, as well as the Prisma methodology. The universe focused on articles published from January 2012 to December 2022 in databases: Scopus, WoS (Web of Science), Scielo, Ebscohost, ScienceDirect, Dialnet, and Google Scholar, in which 22 articles were obtained as a sample for the intervention. The results obtained highlighted the role of gamification in methodology, together with in didactics, to improve the teaching-learning processes of historical science contents, positively affecting motivation, interest, and satisfaction through innovative methodologies, active and immersive learning, as well as an understanding of the dynamics, mechanics, and procedures of the games. It was concluded that gamification is a fundamental strategy in developing historical competence at the preschool, primary, high school, and higher education levels.
Keywords: Gamification; education; learning history; history teaching; bibliographic review